2021
DOI: 10.3389/fpsyt.2021.784370
|View full text |Cite
|
Sign up to set email alerts
|

Treatment of Symptom Clusters in Schizophrenia, Bipolar Disorder and Major Depressive Disorder With the Dopamine D3/D2 Preferring Partial Agonist Cariprazine

Abstract: Cariprazine is currently approved for the treatment of patients with schizophrenia (USA and EU), and for manic, depressive, and episodes with mixed features in bipolar I disorder (USA): several randomized controlled studies have also explored its efficacy in patients with major depressive disorder. This review summarizes its current therapeutic uses and potential advantages for treating the main symptoms of schizophrenia, bipolar I and major depressive disorder, considering its pharmacodynamic properties, effi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 80 publications
0
4
0
1
Order By: Relevance
“…The main reason for this lag behind is the lack of understanding of the diseases' etiopathology. Accumulating data from animal and human studies suggest that the pathophysiology of SCZ, BD and MDD are associated with monoamine abnormality (4)(5)(6)(7). The monoamine hypothesis is supported by the clinical efficacy of many drugs for treating mental illness, however, there is usually a time lag between the acute pharmacological effects and clinical improvement (8).…”
Section: Introductionmentioning
confidence: 99%
“…The main reason for this lag behind is the lack of understanding of the diseases' etiopathology. Accumulating data from animal and human studies suggest that the pathophysiology of SCZ, BD and MDD are associated with monoamine abnormality (4)(5)(6)(7). The monoamine hypothesis is supported by the clinical efficacy of many drugs for treating mental illness, however, there is usually a time lag between the acute pharmacological effects and clinical improvement (8).…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, despite nosological speci city, these disorders can have shared mood disturbance (depression, euphoria, irritability, anhedonia, etc. ), psychotic symptoms (hallucinations, delusions), and cognitive impairment (executive function, and memory impairment) [7][8][9]. Research has suggested that dimensional representations may be more accurate representations than simple categorical descriptions when applied to the diagnosis of psychotic and non-psychotic disorders [10].…”
Section: Introductionmentioning
confidence: 99%
“…In addition to this diagnostic issue, the etiopathology of these diseases is not well understood. Accumulating data from animal and human studies suggest that the pathophysiology of SCZ, BD and MDD are associated with monoamine abnormality [7,[11][12][13]. Although the monoamine hypothesis is supported by the clinical e cacy of many drugs for treating mental illness, there is usually a time lag between the acute pharmacological effects and clinical improvement [14].…”
Section: Introductionmentioning
confidence: 99%
“…The importance of dopaminergic pathways and receptor modulators in the control of neurodegenerative diseases led to the development of drugs such as the classical typical antipsychotic haloperidol ( 1 ), a D 2 receptor antagonist (Ki = 0.89 nM) [ 19 , 20 ], and the atypical antipsychotics aripiprazole ( 2 ) (Ki D 2 = 0.34 nM; Ki D 3 = 0.8 nM) and cariprazine ( 3 ) (Ki D 3 = 0.085 nM; Ki D 2 = 0.49 nM), as partial agonists of D 2 and D 3 receptors [ 21 , 22 , 23 , 24 , 25 , 26 ], approved for the treatment of schizophrenia and bipolar disorder ( Figure 1 ).…”
Section: Introductionmentioning
confidence: 99%